Analisis Efisiensi Produksi dan Distribusi Pakan Ternak dalam Mendukung Ketahanan Pangan Nasional: Review - Irma; Purnama, I; Juanda, F; Ali, A M (Politeknik Negeri Lampung, 2026)
Livestock feed plays a vital role in the national food security system as a key determinant of animal protein availability. However, this sector faces significant challenges, including high production costs reaching 60-70% of total operational expenses, raw material price fluctuations, and dependency on imports. This study aims to analyze factors affecting the efficiency of feed production and distribution and to identify relevant strategies to strengthen food security in Indonesia. The method used is a Systematic Literature Review (SLR) examining literature published between 2013–2023 from various academic databases. The results indicate that production efficiency can be achieved through the diversification of local feed ingredients based on a circular feed economy (such as agricultural waste fermentation), which can reduce costs by up to 30%, alongside the adoption of processing technology mechanization. Regarding distribution, efficiency is attained through logistic route optimization and integrated inventory management to maintain supply chain resilience against market shocks. This study concludes that the synergy between feed technology innovation and logistic system improvement is crucial to ensuring supply stability, affordability of animal protein, and the sustainability of national food security